An indirect treatment comparison of the efficacy of patisiran and tafamidis for the treatment of hereditary transthyretin-mediated amyloidosis with polyneuropathy. (4th March 2019) - Planté-Bordeneuve, Violaine; Lin, Hollis; Gollob, Jared; Agarwal, Sonalee; Betts, Marissa; Fahrbach, Kyle; Chitnis, Madhura; Polydefkis, Michael
ABSTRACT: Background : Hereditary transthyretin-mediated amyloidosis (hATTR amyloidosis) is a progressive, life-threatening disease. Until recently, tafamidis was the only approved pharmacotherapy. Patisiran significantly improved polyneuropathy and quality of life (QoL) in the phase III APOLLO trial. In the absence of direct comparisons, this analysis aimed to evaluate the comparative efficacy of tafamidis and patisiran in hATTR amyloidosis with polyneuropathy. Research design and methods : Randomized controlled trial evidence for tafamidis was identified by systematic literature review. Indirect treatment comparisons were performed using the standard pairwise Bucher method for endpoints used in both APOLLO and the tafamidis Fx-005 trial: change from baseline in Neuropathy Impairment Score-lower limbs (NIS-LL), Norfolk QoL-Diabetic Neuropathy questionnaire (QoL-DN), NIS-LL response, and mBMI vs. placebo. Inter-trial population differences were assessed by sensitivity analysis. Results : The base-case analysis (FAP Stage 1 APOLLO patients vs. intent-to-treat Fx-005 population) suggested patisiran had a greater treatment effect vs. tafamidis for all endpoints, with significant improvements in mean change in NIS-LL (–5.49) and QoL-DN (–13.10) from baseline to Month 18. Similar trends were observed in all sensitivity analyses. Conclusions : In the absence of direct comparisons, this analysis suggests patisiran has a greater treatment effect than tafamidis in patients with hATTR amyloidosis with polyneuropathy.